Comparative and Global Pedagogies
XXIV, 232 p.
Keywords: This book critically examines equality, equity and democracy in education, globally as well as from various perspectives. Globally, there are increasing arguments both for the democratization of education and for the use of education to promote a democratic society. It is argued that democratic schools would better prepare for active citizenship and for a strong civil society which are seen to be the foundation of a democratic state. The book further argues that while there are inspiring examples of schools that engage in peace education or emancipatory pedagogy that work across various ethnic or religious divides, on balance, the forms, structures, ideologies and purposes of formal education interact to make national and international conflict more likely. Drawing upon recent studies in the areas of equity, access and democracy in education, this volume examines the overall interplay between globalisation, democracy and outcomes in education.